Comorbidities in unclassifiable interstitial lung disease - Skovhus Prior, Thomas; Hyldgaard, Charlotte; Torrisi, Sebastiano Emanuele; Kronborg-White, Sissel; Ganter, Claudia; Bendstrup, Elisabeth; Kreuter, Michael (Respiratory research, 2022)
Comorbidities are common in interstitial lung diseases (ILD) and have an important association with survival, but the frequency and prognostic impact of comorbidities in unclassifiable interstitial lung disease (uILD) remains elusive. We aimed to describe the prevalence of comorbidities and assess the impact on survival in patients with uILD. Furthermore, we aimed to identify and characterize potential phenotypes based on clusters of comorbidities and examine their association with disease progression and survival.
Gesehen am 18.05.2022